Hubungan Tingkat Depresi Dengan Gangguan Tidur (Insominia) Pada Lansia Di Upt Panti Werdha “Mojopahit” Kabupaten Mojokerto - Tria Wahyuningrum; Noer Saudah; Lutfi Hermansyah (Akademi Keperawatan Dharma Husada Kediri, 2015)
There are two normal processes of the most important in human life what are eating and sleeping. Although both are very important,it is so routine that we often forget it and will process only after a disturbance in the process then we remember the importance of two conditions. Insomnia is a sleep disorder that is the most commonly found. The incidence will increase by age. Approximately 40% of elderlys complain of insomnia. The research objective analyzed the relationship between the level of depression with sleep disorders (insomnia) of the elderly in UPT Panti Werdha 'Mojopahit' Mojokerto. Design research used analytical correlation with cross sectional approach. The population was 45 respondents Elderly in UPT Panti Werdha „Mojopahit‟ Mojokerto. The sample of this research was 32 people whichwas taken by purposive sampling. Data was taken by the interview using instruments KSPBJ GDS 15 and Scale-irs. After the data was done, it was analyzed by data processing and statistical test of Rank Spearman with SPSS version 16.0. The result showed (0.001) < (0.05), so that H0was rejected.Itwas a relationship with the depressed levels of sleep disorders (insomnia) the elderly in UPT Panti Werdha „Mojopahit‟ Mojokerto,with r = 0.552, which means the correlation was high, strong. Be advised of the research resultis expected in order to elderly can do physical activity and to practice for prevent occurrence of depression in order to avoid insomnia. Keywords: Level ofdepression, sleepdisorder, elderly, and Insomnia